Aetiology And Toxigenicity Of Fusarium Species, The Causal Agent Of Potato Tuber Dry Rot - Yahaya, Noor Fazila Mohamed (2012)
Fusarium dry rot is a worldwide reported disease infecting potato tubers. Thus, many studies have been conducted with a common aim to minimize losses incurred by the disease. The objectives of this study were to confirm the aetiology of Fusarium spp. isolated from potato dry rot and toxigenicity of selected isolates. A series of samplings were conducted in three states in northern Peninsular Malaysia namely Pulau Pinang, Kedah, and Perlis.